Quantification of human infection risk caused by rotavirus in surface waters from Córdoba, Argentina - Prez, Verónica Emilse (2015)
Fecal contamination of water is a worrying problem because it is associated with the transmission of enteric pathogenic microorganisms that can cause many infectious diseases. In this study, an environmental survey was conducted to assess the level of viral contamination by viable enterovirus and rotavirus genome in two recreational rivers (Suquía and Xanaes) of Córdoba, Argentina. Quantitative microbial risk assessment (QMRA) was calculated to estimate the risk of rotavirus infection. Water sampling was carried out during a one-year period, the presence of total and fecal coliforms was determined and water samples were then concentrated for viral determination. Cell culture and indirect immunofluorescence were applied for enterovirus detection and RT-qPCR for rotavirus quantification. Coliform bacteria levels found in Suquía River often far exceeded the guideline limits for recreational waters. The Xanaes exhibited a lower level of bacterial contamination, frequently within the guideline limits. Enterovirus and rotavirus were frequently detected in the monitoring rivers (percentage of positive samples in Suquía: 78.6% enterovirus, 100% rotavirus; in Xanaes: 87.5% enterovirus, 18.7% rotavirus). Rotavirus was detected at a media concentration of 5.7 × 105 genome copies/L (gc/L) in the Suquía and 8.5 × 100 gc/L in the Xanaes. QMRA revealed high risk of rotavirus infection in the Suquía, at sampling points with acceptable and non-acceptable bacteria numbers. The Xanaes showed significantly lower health risk of rotavirus infection but it proved to be a public health hazard. The viral occurrence was not readily explained by the levels of bacteria indicators, thus viral monitoring should be included to determine microbiological water quality. These findings provide the first data of QMRA for recreational waters in Argentina and reveal the need for public awareness of the health implications of the use of the river waters.